การเพิ่มประสิทธิภาพในกระบวนการจัดการอะไหล่คงคลังของงานซ่อมบำรุงเครื่องจักร - พิมพาภรณ์ ณัฐชฎา; ถาพินนา ชัยยะเนตร; เสมศรี ศุภโชค; เรืองฤทธิ์ ชำนาญ; อิ่มสูงเนิน มานะ (วารสารวิชาการเทคโนโลยีอุตสาหกรรม มหาวิทยาลัยราชภัฏสุรินทร์, 2025)
การวิจัยนี้วัตถุประสงค์เพื่อหาความสูญเปล่าในกระบวนการจัดการอะไหล่คงคลังของงานซ่อมบำรุง และเพื่อเพิ่มประสิทธิภาพด้านเวลา , ด้านขั้นตอน , ด้านระยะทาง ในกระบวนการจัดการอะไหล่คงคลังของงานซ่อมบำรุง ดำเนินการวิจัยด้วยการศึกษาสภาพของปัญหาจากบริษัทกรณีศึกษาแห่งหนึ่ง โดยใช้ทฤษฎีและงานวิจัยที่เกี่ยวข้อง และวิเคราะห์สาเหตุของปัญหาเพื่อนำไปสู่การแก้ไขปัญหาด้วยแผนผังแสดงเหตุและผล และใช้แผนภูมิกระบวนการไหลของกระบวนการผลิตร่วมกับหลักการ ECRS มาประยุคใช้ในการปรับปรุงกระบวนการ ผลการวิจัยสรุปได้ดังนี้ จากการใช้แผนผังแสดงเหตุและผลมาวิเคราะห์หาสาเหตุของความสูญเปล่า มีสาเหตุจาก วัตถุดิบ(อะไหล่) , วิธีการทำงาน , ผู้ปฏิบัติงาน และสิ่งแวดล้อมในการทำงาน และใช้หลักการ ECRS พิจารณาความสูญเปล่าในกระบวนการ พบว่า มีขั้นตอนการทำงานที่ซ้ำซ้อนและการจัดการระบบการเบิกจ่ายอะไหล่ไม่มีความชัดเจนเป็นมาตรฐาน และ ด้านการเพิ่มประสิทธิภาพในกระบวนการ พบว่า ด้านขั้นตอนการทำงาน ก่อนปรับปรุง 30 ขั้นตอน หลังปรับปรุงเหลือ 7 ขั้นตอน ลดลงได้ 23 ขั้นตอน ด้านระยะเวลาในการเบิกอะไหล่ต่อชิ้น ก่อนปรับปรุง 25 นาที 36 วินาที หลังปรับปรุง เหลือ 21 นาที 32 วินาที ลดลงได้ 4 นาที 4 วินาที และด้านระยะทาง ก่อนปรับปรุง 280 เมตร หลังทำการปรับปรุงเหลือ 238 เมตร ลดลงได้ 42 เมตร ต่อการเบิกอะไหล่ 1 ครั้ง This research aims to find the waste in the process of managing the inventory of maintenance work and to increase the efficiency in terms of time, steps, and distance in the process of managing the inventory of maintenance work. The research was conducted by studying the problem conditions from a case study company using theories and related research and analyzing the causes of the problem to lead to the solution with a cause and effect diagram and using the production process flow diagram together with the ECRS principle to apply to improve the process and compare the results before and after the improvement. The research results can be summarized as follows: from using a cause and effect diagram to analyzing the causes of waste, there are causes from raw materials (spare parts), work methods, operators and work environment and using the ECRS principle to consider waste in the process, it was found that there are redundant work steps and the management of the spare parts disbursement system is not clear and standard. And in terms of increasing efficiency in the process, it was found that in terms of work procedures, before improvement there were 30 steps, after improvement there were 7 steps, a reduction of 23 steps; in terms of time spent withdrawing spare parts per piece, before improvement there were 25 minutes 36 seconds, after improvement there were 21 minutes 32 seconds, a reduction of 4 minutes 4 seconds; and in terms of distance, before improvement there were 280 meters, after improvement there were 238 meters, a reduction of 42 meters per spare parts withdrawal.